2011
DOI: 10.1186/1754-9493-5-13
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, root-causes, and outcomes of adverse events in surgical units: implication for potential prevention strategies

Abstract: BackgroundWe need to know the scale and underlying causes of surgical adverse events (AEs) in order to improve the safety of care in surgical units. However, there is little recent data. Previous record review studies that reported on surgical AEs in detail are now more than ten years old. Since then surgical technology and quality assurance have changed rapidly. The objective of this study was to provide more recent data on the incidence, consequences, preventability, causes and potential strategies to preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(206 citation statements)
references
References 38 publications
10
185
0
11
Order By: Relevance
“…26,30,53 Checklists for surgery are being pursued due to the increasing recognition that errors in surgery are possible, may result in harm, and may be preventable. The experience with checklists in surgery draws heavily from the aviation industry.…”
Section: Discussionmentioning
confidence: 99%
“…26,30,53 Checklists for surgery are being pursued due to the increasing recognition that errors in surgery are possible, may result in harm, and may be preventable. The experience with checklists in surgery draws heavily from the aviation industry.…”
Section: Discussionmentioning
confidence: 99%
“…Zegers [3] conducted a study in 21 Dutch hospitals in 2004 whose results showed that surgical adverse events represented 65% of all adverse events. In 1999, Gawande et al [4] studied 15,000 randomly medical records of patients from Utah and Colorado hospitals.…”
Section: Contextmentioning
confidence: 99%
“…Death as a result of an AE, prolonged hospital (surgical ward) stay, extra treatment (extra intervention), readmission to the hospital (surgical ward), temporary or permanent disability at the time of discharge (after surgery), suboptimal care, physical injury, mental injury, inconvenience [11,15], Lack of treatment audit before starting procedures, misidentification, exceeded workload, legal liability, and unidentified.…”
Section: Final Impactmentioning
confidence: 99%